INTEGRATING ARTIFICIAL INTELLIGENCE TECHNOLOGIES INTO ENGLISH LANGUAGE TEACHING METHODOLOGY - Hakimov Begmatjon Samijon o‘g‘li (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines the integration of artificial intelligence (AI) technologies into English language teaching methodology. It aims to identify effective pedagogical strategies for incorporating AI tools into language instruction and to evaluate their impact on learners’ communicative competence. The study analyzes current methodological approaches and explores the role of AI in addressing key challenges such as cross-linguistic interference and learner motivation. The findings demonstrate that AI-driven tools contribute to personalized learning, increased engagement, and improved language proficiency. The study concludes that a balanced integration of AI technologies into teaching methodology enhances the overall effectiveness of English language education.